The Herald of literature . or A review of the most considerable publications that will be made in the course of the ensuing winter: with extracts. [By W. Goodwin].; (Scholars' Facsimiles & Reprints, 1966)
Photomechanical reprint of the ed.: London, Murray, 1784. In: W.Godwin, Four early pamphlets (1783-1784).